The Urgency of Establishing a Supervisory Agency for the Implementation of Personal Data Protection in the Implementation of the Personal Data Protection Law - Dhea Cantik; Adhining Prabawati Rahmahani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of digital technology has increased the need for personal data protection in Indonesia, but has not been matched by the presence of an effective supervisory agency as mandated by Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The problem formulation in this study is to analyze the ideal form of the position and independence of the PDP supervisory agency within the concept of an independent state institution and analyze the urgency of establishing a personal data protection supervisory agency in the context of implementing the PDP Law. This study uses a normative juridical method with a legislative approach to Articles 58–61 of the PDP Law, reinforced by scientific literature related to the design of independent state institutions. The results of the study indicate that the authority of the supervisory agency as stipulated in the PDP Law is regulatory, supervisory, investigative, and administrative sanction enforcement, thus requiring the existence of an agency that is institutionally, functionally, and organizationally independent. The increasing number of personal data leaks and the potential for conflicts of interest if the supervisory function is placed under a ministry emphasizes the urgency of establishing an independent supervisory agency. In conclusion, the PDP supervisory agency should ideally be designed as an independent state agency with full authority, and the establishment of a supervisory agency is urgent to ensure the effectiveness of the implementation of the PDP Law.